Current perspectives in semiotics : signs, signification, and communication - Gałkowski, Artur; Kopytowska, Monika Weronika, 1978- (Łódź studies in language, 2018)
"This unique book, inspired by the work of Umberto Eco, one of the greatest semioticians of all times, provides a compelling overview of current developments in semiotic research, bringing together various academic voices and critical reflections on the nature and function of signs, signification, and communication. Contributors, including Eco himself, discuss the status quo of the discipline, its scope, theoretical orientations, and methodological approaches, shedding light on the cognitive and philosophical complexity of the meaning-making process and form-meaning interfaces. The book is an outcome of the SIVO Signum-Idea-Verbum-Opus project initiated by Umberto Eco's keynote address during his visit at the University of Lódz in 2015"- Resumé vydavatel